2008
DOI: 10.1094/phyto-98-4-0475
|View full text |Cite
|
Sign up to set email alerts
|

Biological and Phylogenetic Characterization of Fusarium oxysporum Complex, Which Causes Yellows on Brassica spp., and Proposal of F. oxysporum f. sp. rapae, a Novel Forma Specialis Pathogenic on B. rapa in Japan

Abstract: Although the causal agent of yellows of Brassica rapa (turnip, pak choi, and narinosa) in Japan was reported in 1996 to be Fusarium oxysporum f. sp. conglutinans, this classification has remained inconclusive because of a lack of detailed genetic and pathogenic studies. Therefore, we analyzed the taxonomic position of this organism using Japanese isolates of F. oxysporum complex obtained from diseased individuals of various B. rapa subspecies. Phylogenetic analyses using partial sequences of the rDNA intergeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Although the IGS rDNA has become one of the most popular loci for investigating genetic diversity within the FOSC (Fujinaga et al, 2005;Kawabe et al, 2005;Mbofung et al, 2007;Enya et al, 2008), and its high levels of nucleotide diversity provide a high degree of discriminatory power useful for isolate identification, results of the present study strongly indicate that the homoplastic evolutionary history of this locus obscures accurate phylogenetic relationships within this complex. Of the relatively small number of genes that have been sampled to date within the FOSC (ex., IGS rDNA, EF-1a, polygalacturonases, mitochondrial small subunit ribosomal RNA, phosphate permease, b-tubulin, nitrate reductase, MAT 1 and MAT2), only the EF-1a and IGS rDNA genes appear to have much phylogenetic signal.…”
Section: Discussionmentioning
confidence: 74%
“…Although the IGS rDNA has become one of the most popular loci for investigating genetic diversity within the FOSC (Fujinaga et al, 2005;Kawabe et al, 2005;Mbofung et al, 2007;Enya et al, 2008), and its high levels of nucleotide diversity provide a high degree of discriminatory power useful for isolate identification, results of the present study strongly indicate that the homoplastic evolutionary history of this locus obscures accurate phylogenetic relationships within this complex. Of the relatively small number of genes that have been sampled to date within the FOSC (ex., IGS rDNA, EF-1a, polygalacturonases, mitochondrial small subunit ribosomal RNA, phosphate permease, b-tubulin, nitrate reductase, MAT 1 and MAT2), only the EF-1a and IGS rDNA genes appear to have much phylogenetic signal.…”
Section: Discussionmentioning
confidence: 74%
“…Recent studies showed that phylogenetic analysis of the IGS region sequence was useful for population analysis of the pathogen (Kawabe et al 2005(Kawabe et al , 2007Enya et al 2008). In addition, the mating type locus (MAT1), which regulates sexual reproduction in ascomycete fungi, was cloned from F. oxysporum, and molecular techniques have been developed to demonstrate the presence of the two mating-type idiomorphs, MAT1-1 and MAT1-2 (Arie et al 2000).…”
mentioning
confidence: 99%
“…Fusarium wilt is soil borne fungal pathogen which can sustain many years in the soil without a host (Ignjatov et al, 2012). F. oxysporum has a worldwide distribution and causes severe root rot or vascular wilt in ample range of plant families (Enya et al, 2008;Lievens et al, 2008;Michielse and Rep, 2009). This fungal pathogen infects the seed and early stages of seedling growth, causing seed decay and damping-off (Punja et al, 2004).…”
Section: Introductionmentioning
confidence: 99%